Quasiperiodicity and Chaos in a Generalized Nosé-Hoover Oscillator - Rech P.C.* (2016)
© 2016 World Scientific Publishing Company.This paper reports on an investigation of the two-dimensional parameter-space of a generalized Nosé-Hoover oscillator. It is a mathematical model of a thermostated harmonic oscillator, which consists of a set of three autonomous first-order nonlinear ordinary differential equations. By using Lyapunov exponents to numerically characterize the dynamics of the model at each point of this parameter-space, it is shown that dissipative quasiperiodic structures are present, embedded in a chaotic region. The same parameter-space is also used to confirm the multistability phenomenon in the investigated mathematical model.